Cervicofacial Subcutaneous Emphysema Post Tonsillectomy: A Case Report - Anand Kuppusamy; Thankam Abraham Reshma; Manoj Bhaskar Vishak; A Pushparani (Journal of Clinical and Diagnostic Research)
Tonsillectomy is a routine procedure, commonly performed in children. However, it carries higher risks in older patients due to fibrosis. Post-tonsillectomy, primary or secondary haemorrhage remains the most significant complication. One of the rare but serious complications is cervicofacial Subcutaneous Emphysema (SCE), where air enters the subcutaneous tissue through a defect or weakness in the dissected tissues during or after the surgical procedure. Triggering factors of SCE associated with tonsillectomy include trauma to the tonsillar bed during dissection, excessive pressure from mechanical ventilation or manual bag-mask ventilation, and even excessive coughing or straining in the postoperative period. Though rare, cervicofacial SCE can rapidly progress to life-threatening complications like tension pneumomediastinum, airway obstruction, or even cardiac arrest. In this case report, we present a rare case of SCE following adenotonsillectomy in a six-year-old girl, highlighting the clinical presentation, diagnostic work-up, and management strategies used to successfully treat the patient. The procedure was uneventful; however, post-extubation, the child developed periorbital oedema, neck swelling, and crepitus. Despite this, she remained stable with a normal respiratory rate and oxygen saturation. A neck X-ray was taken to confirm the presence of subcutaneous air. The child was closely monitored, and conservative management was initiated, including supplemental oxygen, corticosteroids, and antibiotics. The child’s condition improved without respiratory compromise, and the emphysema resolved gradually. This report emphasises the importance of recognising this complication early, maintaining vigilance throughout the perioperative period, and implementing appropriate measures to mitigate the risks of this life-threatening condition.